Design and implementation of a 6 degrees of freedom controller for the GRACE system - Retana Calvo, William Jesús (2020)
In this article, the reader can obtain information about the 3D robotic scanner of GroningenUniversity. The design process including the 6 Degrees of freedom control for the movements,also how the light is regulated in order to provide accurate data with an algorithm and a constantcurrent power supply is shown in the document. The implementation and results are showntherefore the reader can analyze the materials and methods for further projects.